2021
DOI: 10.20945/2359-3997000000392
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal crisis and mortality rate in adrenal insufficiency and congenital adrenal hyperplasia

Abstract: Primary adrenal insufficiency (PAI) is characterized by the inability of the adrenal cortex to produce sufficient amounts of glucocorticoids and/or mineralocorticoids. Addison's disease (AD) and congenital adrenal hyperplasia (CAH) are the most frequent disorders in adults and children, respectively. Despite the diagnostic advances and the availability of glucocorticoid and mineralocorticoid replacements, adrenal crisis (AC) is still a potentially lethal condition contributing to the increased mortality, not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
0
10
0
6
Order By: Relevance
“…Hyperkalemia of more than 6 mmol/L can induce fatal cardiac arrhythmias and requires aggressive therapy with intravenous sodium bicarbonate, calcium gluconate, or IV dextrose plus insulin (Parham et al 2006, Miller et al 2008 Education is very important in the management of adrenal insufficiency and the prevention of AC. Patients and families should be informed about CAH, general CAH management, and acute complications which should be taken at home to prevent an adrenal crisis, particularly related to glucocorticoids adjustments in stressful events and AC prevention including administration of emergency glucocorticoid particularly in illness, fever, and any type of stress (Lousada et al 2021). Furthermore, the general practitioners, pediatricians, nurses, and health workers must be aware of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalemia of more than 6 mmol/L can induce fatal cardiac arrhythmias and requires aggressive therapy with intravenous sodium bicarbonate, calcium gluconate, or IV dextrose plus insulin (Parham et al 2006, Miller et al 2008 Education is very important in the management of adrenal insufficiency and the prevention of AC. Patients and families should be informed about CAH, general CAH management, and acute complications which should be taken at home to prevent an adrenal crisis, particularly related to glucocorticoids adjustments in stressful events and AC prevention including administration of emergency glucocorticoid particularly in illness, fever, and any type of stress (Lousada et al 2021). Furthermore, the general practitioners, pediatricians, nurses, and health workers must be aware of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Japan before the NBS and in the UK showed that up to 20% of patients with the SW form of 21OHD developed learning difficulties and intellectual disabilities [16,22,23]. The risk of developing severe salt-wasting increases during the second week of life, and, therefore, an early diagnosis and intervention, preferably during the first week after birth, is of great importance [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol has a half-life of 90 minutes; hence, the adrenal crisis presents within a few hours of cortisol deprivation. As cortisol has multiorgan effects thanks to its pleiotropic nature, the various consequences of its deficiency as explained physiologically are listed below33,34,39: Cortisol has anti-inflammatory effects via suppression of production of various cytokines; hence, adrenal insufficiency results in a rapid surge in cytokine levels, which presents as fevers, myalgia, and loss of appetite. Cortisol promotes demarginalization of neutrophils from endothelial cells into the circulation and promotes apoptosis of eosinophils and lymphocytes, so a cortisol-deficient state leads to neutropenia, eosinophilia, and lymphocytosis. Cortisol is a requisite of the synergistic action of catecholamines; its absence causes vasodilation and hypotension. Cortisol is a stress hormone and in a fight or flight response it amplifies production of glucose, free fatty acids, and amino acids; hence, in adrenal crisis hypoglycemia and reduced free fatty acids are noted. In primary adrenal insufficiency, loss of aldosterone function further exacerbates hypotension, as the body cannot retain sodium and water. …”
Section: Adrenal Crisismentioning
confidence: 99%